Clinical diagnosis and etiology of patients with Chlamydia psittaci pneumonia based on metagenomic next-generation sequencing - Liang, Yueming; Dong, Tingyan; Li, Minjing; Zhang, Peifang; Wei, Xiaoqun; Chen, Haitao; Wang, Yongsi; Gao, Xinglin (Frontiers in Cellular and Infection Microbiology, 2022)
The incidence of severe Chlamydia psittaci (C. psittaci) pneumonia and coinfections is increasing. Early detection of this condition is needed to prevent negative outcomes, along with detailed description of its associated clinical characteristics. Our study contributes by undertaking etiological analysis of patients with C. psittaci pneumonia based on metagenomic next-generation sequencing (mNGS). A retrospective analysis of 30 patients with C. psittaci pneumonia was undertaken and confirmed by mNGS or polymerase chain reaction (PCR). Clinical manifestations of the severe and non-severe C. psittaci pneumonia groups were compared for clinical reference. Etiological analyses were also performed to comprehensively understand pathogeny and coinfection with other respiratory pathogens in C. psittaci patients. The absolute value of lymphocytes (LYM) in the severe group was lower than in the non-severe group. At the same time, neutrophil-to-lymphocyte ratio (NLR), procalcitonin (PCT), alanine aminotransferase (ALT), D-II polymer, brain natriuretic peptide (BNP), myoglobin (MYO), and cardiac troponin I (cTnI) were significantly higher (P < 0.05) in the severe group. mNGS has a broader pathogen spectrum and can more sensitively detect C. psittaci and other low abundance pathogens with a higher positive detection rate (100%, 13/13 vs. 46%, 6/13, P < 0.05) than conventional culture methods. mNGS detected the following dominant species associated with C. psittaci in patients: bacteria (53.2%, 39% gram-positive, 61% gram-negative), fungi (12.9%) and viruses (33.9%). A total of 73.3% (11/15) of patients had suspected coinfections, with a coinfection rate of 91.7% (11/12) in the severe group. No coinfection or death occurred in the non-severe group. Prognosis in the severe group was poor, with a mortality rate of 27.3% (3/11) for patients with coinfection. Eight of eleven patients with coinfections (72.7%) recovered. In conclusion, the clinical symptoms of severe C. psittaci pneumonia manifested as abnormal inflammatory indicators, impaired liver function, myocardial injury, coagulation, and relatively low immune responses. The higher proportion of patients with coinfections in our study supports the use of mNGS for comprehensive early detection of respiratory infections in patients with C. psittaci pneumonia. Simultaneous early identification of coinfections would further improve the clinical treatment of these patients.